Qual é o modelo legal das licitações no Brasil?: as reformas legislativas federais no sistema de contratações públicas - Rosilho, André Janjácomo (2011)
The research aims to understand the characteristics and objectives of the current legal model of public procurement in Brazil. It wants to analyze the course and the context of federal legislative reforms undertaken on the subject. The research identifies that up to the enactment of Law nº 8.666/93, the institute of public bidding was characterized by a process of increasing legalization focused, on one hand, in the expansion of the duty to bid and, on the other hand, the unification of the bidding system in the public administration. It also noted that there was a trend whose apex was reached when Law nº 8666/93 was passed, aimed at restricting the discretion of the public administrator to decide, in specific cases, the best way to bid. Also notes that special interest groups – the average emerging contractors – were able to capture the legalization process of the procurement system, and influence it in their favor. Finally, it showed that the general legislation on public procurement have been built on a model of law excessively standardized and rigid, that was responsible, directly and indirectly, to the fragmentation of the procurement system.